The short- and long-term outcomes of pancreaticoduodenectomy for distal cholangiocarcinoma - Skalicky, Pavel; Urban, Ondrej; Ehrmann, Jiri; Svebisova, Hana; Klos, Dusan; Tesarikova, Jana; Neoral, Cestmir; Knapkova, Katerina; Lovecek, Martin (Biomedical papers, 2022)
Background. The aim of the study was to calculate the short-term and long-term outcomes of curative-intent surgery in distal cholangiocarcinoma (DCC) patients to identify potential prognostic factors. Patients and Methods. A retrospective cohort study of 32 consecutive DCC patients treated with pancreaticoduodenectomy between 2009-2017. The clinicopathological and histopathological data were evaluated for prognostic factors using the univariable Cox regression analysis. The Overall Survival (OS) was estimated using the Kaplan-Meier analysis. Results. The study comprised a total of 32 patients, with a mean age of 65.8 ( extpm 9.0) years at the time of surgery. R0 resection was achieved in 25 (86.2%) patients, 19 (65.5%) patients received adjuvant oncological therapy. The OS rates at 1, 3 and 5 years were 62.5%, 37.5% and 21.9%, respectively. The 90-day mortality was 3/32 (9.4%) accounting for one-fourth of the first-year mortality rate. The median OS was 28.5 months. The only statistically significant prognostic factor was vascular resection, which was associated with worse OS in the univariable analysis (HR: 3.644; 95%-CI: 1.179-11.216, P=0.025). An age less than 65 years, ASA grade I/II, hospital stay of fewer than 15 days, R0 resection, lymph node ratio less than 0.2 and adjuvant oncological therapy tended to be associated with better OS but without statistically significant relevance. Conclusion. The main factor directly influencing the survival of DCC patients is surgical complications. Surgical mortality comprises a significant group of patients, who die in the first year following pancreaticoduodenectomy. Vascular resection is the most important negative prognostic factor for long-term survival.
Keywords: cholangiocarcinoma; pancreaticoduodenectomy; long-term survival; prognostic factor